Base promoted successive dealkylation steps of molybdenum alkoxides leading to a row of novel 1D and 2D polymeric frameworks of potassium–molybdenum oxomethoxides. (8th January 2015) - Kuznetsov, Denis A.; Kovaleva, Nadezhda V.; Fedyanin, Ivan V.; Lyssenko, Konstantin A.; Bazhenova, Tamara A.
Abstract : Graphical abstract: A series of heterometallic potassium–molybdenum oxo-alkoxides with various K/Mo stoichiometries, arranged into different supramolecular frameworks, was synthesized by the reaction of MoCl5 methanolysis in the presence of KOCH3 . An unusual example of the reaction of non-hydrolytic oxo-group formation affording a mixed-bridged oxo-alkoxo compound is presented. Abstract: The MoCl5 methanolysis reaction, in the presence of basic agents providing weakly alkaline media, leads to the formation of a Mo–Mo triply bridged anionic dimeric complex with a solvated potassium counter-ion, [K(CH3 OH)2 Mo2 O2 (μ2 -OCH3 )3 (OCH3 )4 ] (1 ), that represents the first structurally characterized Mo–K oxoalkoxide . Here we describe its further reactivity, i.e. the MoCl5 methanolysis reaction in the presence of an additional equivalent of base which leads to demethylation of the one of μ2 -bridging alkoxides, thus giving an unusual oxo-, dimethoxo-bridged cluster, [K2 (CH3 OH)Mo2 O2 (μ2 -OCH3 )2 (μ2 -O)(OCH3 )4 ] (2 ). Subsequent transformation with the generation of the formally Mo–Mo 4− species in [K4 (CH3 OH)6 Mo2 O2 (μ2 -O)2 (OCH3 )2 (CO3 )2 ] (3 ) was achieved via addition of an extra amount of base in the presence of potassium carbonate along with providing more vigorous reaction conditions.